2020
DOI: 10.1075/jslp.19010.sil
|View full text |Cite
|
Sign up to set email alerts
|

The role of talker variability in the perceptual learning of Mandarin tones by American English listeners

Abstract: Research on segmentals has suggested that a key component of High Variability Phonetic Training (HVPT) is high talker variability. However, the extent to which high talker variability improves perception of tones is unclear. This study examined the effects of high talker variability on the perception of Mandarin tones (Tones 1–4) by English-speaking listeners. A training paradigm that used multiple talkers (multitalker group) was compared with a parad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…One study was conducted by Macdonald (2012) who found that only multiple-talker training effects were retained one month later when training native English-speaking learners on French vowel contrasts (/u/ vs. /y/ and /ɑ/ vs. /ɔ/). Another study is Silpachai (2020) who trained English speakers who have limited tonal language experience to perceive Mandarin tones (Tones 1-4). The results showed that the multiple-talker group retained their learning of Tone 2, 3, and 4 six months after training, while the single-talker group also retained the learning of Tone 3 and 4.…”
Section: The Role Of Input Variability In L2 Speech Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…One study was conducted by Macdonald (2012) who found that only multiple-talker training effects were retained one month later when training native English-speaking learners on French vowel contrasts (/u/ vs. /y/ and /ɑ/ vs. /ɔ/). Another study is Silpachai (2020) who trained English speakers who have limited tonal language experience to perceive Mandarin tones (Tones 1-4). The results showed that the multiple-talker group retained their learning of Tone 2, 3, and 4 six months after training, while the single-talker group also retained the learning of Tone 3 and 4.…”
Section: The Role Of Input Variability In L2 Speech Learningmentioning
confidence: 99%
“…One complication here is that increased variability may come at a processing cost Fuhrmeister & Myers, 2017, 2020Luthra et al, 2021;Sadakata & Mcqueen, 2014;Saltzman et al, 2021). Across domains of visual perception, auditory perception, motor learning, language, inductive reasoning, problem solving, and computational modeling, a general observation is that increased input variability may come at a cost of initially hindering learning but often show subsequent benefits in generalization (Raviv et al, 2022).…”
Section: Introductionmentioning
confidence: 99%